2022
DOI: 10.3390/su14138193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Knowledge, Attitude, and Behavior of Workers Regarding COVID-19 Precautionary Measures on Food Safety at Foodservice Establishments in Jordan

Abstract: The novel coronavirus (COVID-19) pandemic has caused sequential ripples of public health concern worldwide. Restaurant owners and workers have been significantly affected by safety regulations which have governed the activities of both employees and consumers. The objective of this study was to investigate the knowledge, attitude, and practices (KAP) of restaurant owners and workers in the context of COVID-19 and assess the effect of COVID-19 precautions on the implementation of food safety measures at foodser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Our survey revealed that near half of the knowledge of hygiene practices is poorly understood by food workers, which implies that the knowledge of food handling possessed by professionals who handle food is significantly inadequate. This result is similar to the results of Habte et al ( 5 ) survey on food handlers’ knowledge in Ethiopia (mean correct rate = 58.4%) and Olaimat et al ( 32 ) survey on food handlers’ knowledge in Jordan, but lower than the results of Ferreira et al ( 13 ) survey on food workers in Brazil (mean correct rate = 72.2%). Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al ( 13 ) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training.…”
Section: Discussionsupporting
confidence: 88%
“…Our survey revealed that near half of the knowledge of hygiene practices is poorly understood by food workers, which implies that the knowledge of food handling possessed by professionals who handle food is significantly inadequate. This result is similar to the results of Habte et al ( 5 ) survey on food handlers’ knowledge in Ethiopia (mean correct rate = 58.4%) and Olaimat et al ( 32 ) survey on food handlers’ knowledge in Jordan, but lower than the results of Ferreira et al ( 13 ) survey on food workers in Brazil (mean correct rate = 72.2%). Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al ( 13 ) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training.…”
Section: Discussionsupporting
confidence: 88%
“…In another study, it was found that only 20% of workers possessed good knowledge, 56% had positive attitudes, and 55% had good practices. In general, it was observed that the precautions and preventive measures put in place during the pandemic improved the application of key food safety regulations within their workplaces [ 24 ]. Also, more training is required to prevent the spread of COVID-19 and foodborne pathogens via the application of good hygienic practices that improve food safety, reducing illnesses and food waste while maintaining food security and economic sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Ref. [ 24 ] only 35% of workers know that the hand washing duration period is at least 20 s. It has been indicated that hand hygiene is more important than any other steps during cleaning and disinfecting food surfaces in terms of controlling the spread of pathogens. That is because hands are considered the main reason for spreading pathogenic microorganisms [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public awareness campaigns on food hygiene and safety are standard practices in local markets in Ghana. Food hygiene and safety awareness programs were increased during the COVID-19 pandemic to minimize the impact of foodborne illnesses [ [33] , [34] , [35] ] and in local markets in Ghana [ [36] , [37] , [38] ]. The high knowledge of foodborne illnesses transmission in this study can be attributed to the COVID-19 pandemic awareness creation.…”
Section: Discussionmentioning
confidence: 99%